Capital structure as a mediation variable: Profitability and liquidity on company value in real estate companies in Indonesia stock exchange - Putra, I Gede Wibawa Reska; Sedana, Ida Bagus Panji (International research journal of management, IT and social sciences, 2019)
The purpose of this study is to determine the effect of variable profitability, liquidity, and capital structure on the firm value in real estate companies listed on the Indonesia Stock Exchange (IDX). The population of this study is a real estate company listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The method of determining the sample in this study used a purposive sampling method, with several predetermined criteria, then the number of selected samples was 26 companies. Data collection is done using the method of non-participant observation. The data analysis technique used is path analysis which is an extension of the multiple linear regression analysis techniques. Based on the results of the analysis of the study shows that the variables of profitability, liquidity, and capital structure have a positive and significant effect on firm value. The results of the Sobel test also show that the capital structure variable is able to mediate the relationship between profitability and liquidity towards firm value.